The Interaction of Zhenshan Sacrifice鎮山祭祀 with Buddhism and Taoism in Patriarchal Traditional Religion - Renzhong Cui (Asian Journal of Philosophy and Religion, 2023)
About the record of Zhenshan鎮山 has a long history, and it has gone through the establishment from a general high mountain to the layout of Twelve Zhenshan, Nine Zhenshan, Four Zhenshan, to the final establishment of the pattern of the Five Great Zhenshan. In this process, the Zhenshan Sacrifice have also been gradually developed and improved. Placing Zhenshan Sacrifice in patriarchal traditional religion can further clarify the attribution of Zhenshan Sacrifice and their position within it, which is specifically reflected in the imperial enfeoffment of Zhenshan and the activities of sending officials to offer sacrifice throughout the ages. At the same time, Buddhism and Taoism also have rich expressions and interactions with Zhenshan Sacrifice in Patriarchal Traditional Religion.